THE LEGAL STANDING OF BUSINESS ACTORS IN A DIGITAL MARKET ACCORDING TO LAW NO. 5 OF YEAR 1999 ON THE PROHIBITION OF MONOPOLISTIC AND UNHEALTHY BUSINESS COMPETITION PRACTICES - Widhiyanti, Hanif Nur; Dheyanoor, Pungki Febriana (Arena Hukum, 2023)
Through a Digital Market, the commercial activities of business actors are conducted virtually and can have a global reach. Commercial activities that no longer require face-to-face meetings in conducting transactional activities and that involve cashless payment methods have made it possible for business actors to transgress the jurisdictional boundaries of a state as they conduct their business activities. Digital Market becomes an inevitability as well as a legal matter in the application of Law No. 5 of Year 1999, particularly in relation to the legal standing of business actors. The consideration is that in the context of a virtual market, geographical boundaries no longer firmly limit the jurisdictional territory of a state. Therefore, the discussion regarding the characteristics of a Digital Market and the legal standing of business actors in a Digital Market becomes an urgent need. Through juridical normative research, this article intends to analyze the characteristics of a Digital Market and the legal standing of business actors in a Digital Market according to Law No. 5 of Year 1999.